Be fierce : stop harassment and take your power back - Carlson, Gretchen, 1966- (New York ; Nashville : Center Street, 2017)
The star news anchor recalls her career-risking decision to speak out against sexual harassment in the workplace, shares the stories of women who have faced similar challenges, and outlines recommendations from lawyers, psychologists, and other professionals on how to resist injustice.
"When star news anchor, journalist, mother of two, and former Miss America Gretchen Carlson spoke up about sexual harassment in the workplace, she had no idea what lay ahead. But now, inspired by her actions, the floodgates have opened and thousands of women are joining her to Be Fierce and reclaim their power against any abuse or injustice. In BE FIERCE, Gretchen shares her own experiences, as well as powerful and moving stories from women in many different careers and fields who decided they too weren't ready to shut up and sit down. Gretchen became a voice for the voiceless. In this revealing and timely book, Gretchen shares her views on what women can do to empower and protect themselves in the workplace or on a college campus, what to say when someone makes suggestive remarks, how an employer's Human Resources department may not always be your friend, and how forced arbitration clauses in work contracts often serve to protect companies rather than employees. Her groundbreaking message encourages women to stand up and speak up in every aspect of their lives. Gretchen also discusses why this fight will require both women and men working together to ensure that our daughters and sons will have a brighter future. BE FIERCE is a cultural movement and a motivating testament to what we can accomplish if we collectively decide to become warriors in the path for a better future. The time is now. Take back your life, your career, and your dignity."--Jacket.
Introduction: Are you done taking sh*t? -- Speaking the unspeakable -- You can't break a badass -- Don't rob my dream! -- You have the right -- "Asking for it" -- Forced into silence -- Men who defend -- Enough already! -- Our children are watching -- Be fierce -- Join me.
Includes bibliographical references (pages 209-229) and index.
Nonfiction
Keywords: Carlson, Gretchen, -- 1966-; Carlson, Gretchen, -- 1966-; Sexual harassment of women; Women television journalists -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts; BIOGRAPHY & AUTOBIOGRAPHY -- Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY -- Political; BIOGRAPHY & AUTOBIOGRAPHY -- Rich & Famous; BIOGRAPHY & AUTOBIOGRAPHY -- Women; BUSINESS & ECONOMICS -- Women in Business; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE -- Sexual Abuse & Harassment; SOCIAL SCIENCE -- Women's Studies; Sexual harassment of women; Women television journalists; United States; Autobiographies; Biography; Autobiographies; Autobiographies